Research of the pre-launch powered lubrication device of major parts of the engine D-240; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Korchuganova M. A. Marina Anatolievna; Syrbakov A. P. Andrey Pavlovich; Tkachev A.; Zorina T. (Advanced technologies and equipment for agro-industrial complex (AIC) and mining, 2015)
Title screen